IMUNISASI MENURUT HUKUM ISLAM KONTROVERSI IMUNISASI VAKSIN POLIO IPV INJEKSI YANG MENGANDUNG ENZIM BABI - Imam Fawaid; Farhatin Masruroh (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2020)
Vaccinating is one of effort to increase body invulnerability andcontagion remove. Vaccinating can be done by inseminated vaccineapplication or is dropped on child mouth. Between vaccine type that isutilized is polio's vaccine special (IPV) deep hypodermic processes itsmakings utilize indigenous enzyme ham enzyme. Ulama variably opiniondeeping to behave this case. There is that says bastard, since seeingmarks sense ham element that is utilized, which well al qur ’ an and alsohadits is Prophet bears out that that animal is prohibited. While fatwahMUI says kosher but with severally stipulates rule who shall accomplishto base syar's theorems ’i. It is attributed as preventif's action to itshappening serious disease on child.